IDENTIFYING INADEQUATE RESPONSE AMONG ULCERATIVE COLITIS PATIENTS ON AN ADVANCED THERAPY IN A REAL-WORLD ADMINISTRATIVE CLAIMS DATABASE. (21st January 2021) - Naegeli, April; Hunter, Theresa; Grabner, Michael; Isenberg, Keith; Shan, Mingyang; Teng, Chia-Chen
Abstract: Objectives: The purpose of this analysis was to assess the frequency of inadequate response (IR) over 1 year from advanced therapy (AT) initiation among ulcerative colitis (UC) patients in the United States using a claims-based algorithm. Baseline factors associated with IR to an AT were also analyzed. Methods: This was a retrospective cohort study using claims data from the HealthCore Integrated Research Database (HIRD®). Adult patients with UC who initiated an AT (TNFi: adalimumab, golimumab, infliximab; non-TNFi: vedolizumab; other agent: tofacitinib) from 7/1/2016 to 8/31/2018 and had continuous enrollment ≥6 months before and ≥12 months after index date (date of first AT claim) were included. The index AT was defined as the first AT prescribed during the study time period. The claims-based algorithm used in this study to identify IR was originally developed and validated in rheumatoid arthritis 1, and was modified for UC patients. Patients were identified as having IR to their index AT if during the 12 months after index date they had one or more of the following: low adherence (defined as proportion of days covered (PDC)<80%), switched/added new AT, added a new conventional therapy, increased dose/frequency of AT, addition or dose increase of oral glucocorticoids, used a new pain medication, or had surgery for UC. Baseline patient characteristics were compared between responders and IRs using chi-square tests for categorical variables and t-tests for continuous variables. A multivariable logistic regression model was constructed to identify baseline characteristics associated with IR to the index AT. Results: A total of 1, 692 UC patients were included in this analysis. Mean age was 42 years, 52% were male, 78% initiated a TNFi, and 22% initiated a non-TNFi as their index AT (Table 1). Over the 1-year follow-up period, 63% of UC patients had an IR to their AT: 42% of patients had low adherence, 24% switched/added a new AT, 18% added a new conventional therapy, 13% had a dose/frequency increase of their index AT, 14% had an addition/dose increase of oral glucocorticoids, 8% used a new pain medication, and 2% had surgery. Inadequate responders were more likely to be prescribed a TNFi (odds ratio (OR)=2.76; p<0.001), and have a higher baseline Quan-Charlson Comorbidity Index (OR=1.15; p=0.015); while patients with baseline use of azathioprine were more likely to be responders (OR=0.72; p=0.025) (Table 2).